PENERAPAN MANAJEMEN PESERTA DIDIK PADA SEKOLAH MENENGAH ATAS - Cindy, Agustin Hanivia; Aisyah, Viana Putri (STKIP Pesisir Selatan, 2024)
Learner management can function as a platform that promotes growth, quality, and achievement in educational institutions. Students are effectively supervised and controlled to ensure that educational institutions can accurately assess the progress of students' achievements. Student management is the administrative process that encompasses all actions related to students, starting from their enrollment in school until their graduation. This process involves many tasks such as coaching, planning, evaluation, and transfer. The objective of this study is to ascertain the administrative procedures involved in managing high school students. The study methodology employed is descriptive qualitative, utilizing a phenomenon-oriented research technique. The research employs data gathering approaches such as observation, interviews, and documentation. The research findings indicate that nearly all schools have successfully implemented student management systems that are tailored to the unique characteristics of each school. The student management process encompasses several tasks such as student planning, student acceptance and selection, student grouping, attendance and absence management, student evaluation, extracurricular activities and OSIS, management of student transfers and dropouts, as well as handling graduates and alumni.